The STUDY OF THE NATURE AND PROSPECTS OF PRACTICAL APPLICATION OF THE MAGNETOCALORIC EFFECT IN ENERGY-EFFICIENT COOLING SYSTEMS: STUDY OF THE NATURE AND PROSPECTS OF PRACTICAL APPLICATION OF THE MAGNETOCALORIC EFFECT IN ENERGY-EFFICIENT COOLING SYSTEMS - Avazov, Bobomurod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents the results of the analysis of the magnetocaloric effect (MCE), its physical nature, and the prospects for its application in magnetic cooling systems. Special attention is paid to the thermodynamic relationships describing the change in temperature of magnetic materials during adiabatic magnetization and demagnetization. Materials with giant MKE, including rare-earth magnetics and their alloys, were considered, with an assessment of their suitability for use in household and industrial magnetic refrigeration units. It has been shown that the efficiency of MKE depends on magnetic entropy, heat capacity, and the properties of the working medium. Modern approaches to calculating and experimentally determining MKE are presented, as well as models of magnetic refrigeration machines based on cyclic magnetization and demagnetization of working bodies.